Evaluation of genscript cpass and immusafe covid+ assays for the detection of neutralizing antibody titers against sars-cov-2 in individuals with second and booster doses of BNT162b2 - Salleh, Faraazlin (2023)
The coronavirus disease outbreak has caused millions of deaths and widespread unemployment globally. Vaccination boosts neutralizing antibody titers and reduce the spread of SARS-CoV-2 virus. Neutralizing antibodies inhibit the interaction of the virus by blocking the binding between the receptor binding domain of SARS-CoV-2 and the host receptor surface. The primary aim of this study was to evaluate GenScript cPass and ImmuSAFE COVID+ assays for detecting neutralizing antibody titers using samples collected from second and booster doses of the BNT162b2 vaccine. GenScript cPass and ImmuSAFE COVID+ assays are the current neutralization tests on the market. The evaluation of neutralization tests demonstrated a statistically significant increase in neutralizing antibodies after the booster dose using GenScript cPass. In contrast, ImmuSAFE COVID+ showed a decline in neutralizing antibodies after the booster dose. The demographic data between age and gender against neutralizing antibody titers was also evaluated, showing no correlation between gender and age towards neutralizing antibodies. The study concludes that GenScript cPass and ImmuSAFE COVID+ assays demonstrate the ability in determining neutralizing antibody titers post-vaccination.